ЛІНГВОКУЛЬТУРНІ АСПЕКТИ У РЕКЛАМУВАННІ ЗАМІННИКІВ КАВИ „FRANCK / ФРАНКК” (ЗА МАТЕРІАЛАМИ РЕКЛАМНИХ ОГОЛОШЕНЬ В УКРАЇНСЬКИХ ПЕРІОДИЧНИХ ВИДАННЯХ ПЕРШОЇ ПОЛОВИНИ ХХ СТ.) - Ткач, Людмила Олександрівна; Закутня, Анна; Сулима, Софія Петрівна (Center of Modern Pedagogy "Learning Without Borders" (Canada), 2020)
Almost 200 years have passed since the German company «Heinrich Franck Sohne» G.m.b.H. was registered in 1828 and started the production of chicory substitute coffee. During the period 1879 and 1918, «Heinrich Franck Sohne» company actively developed its enterprise chain all over Europe and the United States. Coffee substitutes advertisement was published not only by German publications, but also by Austrian, Hungarian, Czech, Slovak, Romanian, Croatian, Polish, and Ukrainian publication establishments. In different countries, advertisement of the same product differed not only in the language of writing the text, but also in graphic design and advertising narratives. Ukrainian-language advertising of coffee substitutes «Franck» has been known since the end of the ХІХth century (according to the publications of the Lviv editions «Dilo», «Krynytsia», etc., the diaspora newspaper «Svoboda», etc.). The main features of these texts are the following: 1) a combination of different language codes; 2) stylistic expressiveness in the formulation of advertising slogans and clichés; 3) complete compositional correspondence to the typical features of modern advertising as a separate functional style of written language, etc.
LINGUOCULTURAL ASPECTS IN THE ADVERTISING OF COFFEE SUBSTITUTES «FRANCK» (BASED ON ADVERTISEMENT OF UKRAINIAN PERIODICALS’ MATERIALS DATED OF THE EARLY XX CENTURY)
Keywords: Ukrainian advertisement of the early XX century; coffee substitues advertisement of «Franck»; advertisement of the «Heinrich Franck Sohne» trademark; multicoding of advertising text; Ukrainian advertising style; the newspaper «Dilo»; the newspaper «Svoboda»; Polish artist Zofiya Stryenska